Relationship Between Professional Competence of Widyaiswara with Learning Outcome of Cooperative Training Participants for Young Generations in Cooperative Training Center UPTD West Sumatra Province - Yola Handani; Vevi Sunarti (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
This research is motivated by the low learning outcomes of the Cooperative Training Participants for the Young Generation at the UPTD Cooperative Training Center, West Sumatra, this is presumably due to the low professional competence of widyaiswara. This study aims to: describe the professional competence of widyaiswara, learning outcomes of training participants' learning outcomes, and see the relationship between widyaiswara's professional competencies and learning outcomes of Cooperatives training participants for the Young Generation at UPTD Cooperative Training Center of West Sumatra. The research population is the learning residents who are registered as participants in the Cooperative Training for the Young Generation in 2020 totaling 35 people and a sample of 25 training participants who were taken using a sampling technique, namely simple random sampling. Data collection techniques in the form of a questionnaire with a questionnaire tool. Data analysis technique with percentage formula and rank order correlation. The results showed that: (1) the professional competence of widyaiswara was low, (2) the learning outcomes of the training participants were low, (3) there was a significant relationship between the professional competence of the widyaiswara and the learning outcomes of the Cooperatives training participants for the Young Generation at UPTD Cooperative Education and Training Center Sumatra. West. It is recommended for institutions to be able to pay attention to matters relating to the achievement of training participants' learning outcomes so that the learning outcomes achieved by training participants are maximized, and it is recommended for widyaiswaras to improve their competencies in order to improve training participants' learning outcomes.Keywords: widyaiswara professional competence, learning outcomes, education and training